Complete Controllability for Fractional Evolution Equations - Xia Yang; Haibo Gu (Abstract and Applied Analysis)
The paper is concerned with the complete controllability of fractional evolution equation with nonlocal condition by using a more general concept for mild solution. By contraction fixed point theorem and Krasnoselskii's fixed point theorem, we obtain some sufficient conditions to ensure the complete controllability. Our obtained results are more general to known results.